2018
DOI: 10.17130/ijmeb.2018137572
|View full text |Cite
|
Sign up to set email alerts
|

KAMUSAL, ÖZEL ve YABANCI SERMAYELİ BANKALARIN KULLANDIRDIKLARI TARIMSAL KREDİLERİN TARIMSAL ÜRETİME ETKİSİ: EGE BÖLGESİ NE YÖNELİK PANEL VERİ ANALİZİ

Abstract: Çalışmanın amacı tarımsal kredi rakamlarında ortaya çıkan artışın, tarımsal üretime ne kadar katkı sağladığının ekonometrik model aracılığıyla incelenmesidir. Çalışmada, kamusal, özel ve yabancı sermayeli bankaların Ege bölgesi illerinde kullandırdıkları tarımsal kredilerin Ege bölgesindeki tarımsal üretime etkisi panel veri analiziyle araştırılmıştır. Analiz sonuçlarına göre kamusal sermayeli banka kredilerindeki yüzde 10'luk artış tarımsal üretimi % 3.2, özel sermayeli banka kredilerindeki yüzde 10' luk artı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…Accordingly, 17% of the difference between long-term, equilibrium, or the desired amount of agricultural GDP and the current or observed agricultural GDP is reduced each year. Findings in the literature show that agricultural credits positively affect agricultural productivity (SHAH et al, 2008;AYAZ & HUSSAIN, 2011;SALEEM & JAN, 2011;AGUNUWA et al 2015;AWOTIDE et al 2015;CHISASA & MAKINA, 2015;NNAMOCHA & EKE, 2015;UDOKA et al 2016;OGBUABOR & NWOSU, 2017;DURAMAZ & TAS, 2018;ADEMOLA, 2019;TAMBI & BIME, 2019). IQBAL et al (2003), SIAL et al (2011, REHMAN et al (2017), KOC et al (2019); REHMAN et al (2019), found that agricultural credits have a positive and statistically significant effect on agricultural GDP.…”
Section: Ols Regression For Parameter Relationsmentioning
confidence: 99%
“…Accordingly, 17% of the difference between long-term, equilibrium, or the desired amount of agricultural GDP and the current or observed agricultural GDP is reduced each year. Findings in the literature show that agricultural credits positively affect agricultural productivity (SHAH et al, 2008;AYAZ & HUSSAIN, 2011;SALEEM & JAN, 2011;AGUNUWA et al 2015;AWOTIDE et al 2015;CHISASA & MAKINA, 2015;NNAMOCHA & EKE, 2015;UDOKA et al 2016;OGBUABOR & NWOSU, 2017;DURAMAZ & TAS, 2018;ADEMOLA, 2019;TAMBI & BIME, 2019). IQBAL et al (2003), SIAL et al (2011, REHMAN et al (2017), KOC et al (2019); REHMAN et al (2019), found that agricultural credits have a positive and statistically significant effect on agricultural GDP.…”
Section: Ols Regression For Parameter Relationsmentioning
confidence: 99%
“…In the literature, several studies examine the nexus between agricultural loans and agricultural production. Indeed, these studies (Sogo-Temi and Olubiyo, 2004; Das et al , 2009; Ahmad, 2011; Terin et al , 2014; Ekokotu Vincent and Lucky, 2015; Chandio et al , 2016a, b, 2018, 2020; Rehman et al , 2017a, b; Duramaz and Taş, 2018) reveal that there is a relationship between agricultural loans and agricultural production and the agricultural loans positively affect agricultural production. On the other hand, many studies (Carter, 1989; Carter and Wiebe, 1990; Feder et al , 1990; Binswanger and Khandker, 1995; Pitt and Khandker, 1996; Khandker and Faruqee, 2003; Awotide et al , 2015; Khandker and Koolwal, 2016; Narayanan, 2016) argue the benefits of agricultural loans in developing countries and indicate that agricultural loans rise productivity and farmer incomes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to see the effect of this loan volume expansion on the agricultural production value, we include the 2008 global crisis year in the scope of analysis. As a matter of fact, in the studies examining the relations between the agricultural loans and agricultural production value (Duramaz and Taş, 2018;Terin et al, 2014), we see that the 2008 global crisis year was included in the data.…”
Section: Methodsmentioning
confidence: 97%
“…Republic of Turkey Ziraat Bank gave almost all agricultural loans in Turkey until the mid-2000s (Güneş and Artukoğlu, 2010). After 2002, agricultural loans have started to increase, especially with the provision of loans to the agricultural sector by private banks and improvements in loan terms (Terin et al, 2014;Duramaz and Taş, 2018). There has been a significant increase in agricultural loan balances due to the interest shown by private banks in the sector and the subsidized loan application that has been implemented since 2004.…”
Section: Introductionmentioning
confidence: 99%